Influence of Elevated Curing Temperatures on Ultrasonic Pulse Velocity in Portland Cement and Fly Ash Concretes - Elsageer, Mohammed; Omar, Ali (Journal of Pure & Applied Sciences, 2026)
Ultrasonic Pulse Velocity (UPV) is a well-established non-destructive testing (NDT) technique that has been employed for over seven decades to evaluate the integrity and quality of concrete structures. It is extensively utilised to detect internal cracks, voids, and other discontinuities, as well as to monitor deterioration arising from exposure to aggressive chemical environments or repeated freeze–thaw cycles. Moreover, UPV is commonly applied as an indirect method for estimating the compressive strength of concrete. This paper investigates the influence of temperature on the development of UPV in Portland cement and fly ash concretes immediately after casting, with the objective of predicting early-age compressive strength. The technique was employed to assess the effect of varying curing temperatures on the early evolution of pulse velocity in these materials. In addition, the correlation between UPV and compressive strength was analysed, highlighting that the reliability of strength prediction is strongly dependent on the accuracy of UPV measurements. The paper demonstrates that ultrasonic pulse velocity (UPV) is a reliable and sensitive method for assessing early-age behaviour and predicting compressive strength in Portland cement and fly ash concretes (15–45% replacement). Curing temperature significantly accelerates UPV development, while fly ash delays early-age response without altering the overall trend. A strong exponential correlation confirms the robustness of UPV for strength estimation, highlighting its practical value for non-destructive evaluation and optimisation of curing conditions.